Implementation of Laundry Services Information Systems for MSMEs in Cekok Village - Ponorogo City - Kudhori, Ahmad; Pandowo, Hedi; Guntur Wibowo, Sundaru; Kusumaningrum, Dian (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
The Community Service Program (PKM) is focused on designing desktop -based information systems and equipped with Android -based applications for Aiko Laundry. For this Android application is a platform based on a local data base that is specifically designed can be accessed online to help Aiko Laundry in managing and marketing clothing laundry services. With the online booking feature, communication with customer service, and customer testimonials, customers can easily order laundry services, interact with customer service for special questions or requests, and provide testimonials about their experience with Aiko Laundry services. The main purpose of designing desktop and Android application Aiko Laundry Information Systems is to make a useful contribution to Aiko Laundry. Service is carried out by focusing on three special targets. First, designing and developing desktop -based applications and equipped with an Android application based on Aiko Laundry Information Systems. Second, compile a manual guide that provides complete guidelines on the use of Aiko Laundry information systems. Third, presenting presentations and conducting training to the Aiko Laundry Team to ensure a good understanding of the use of information systems. The implementation of laundry service information systems shows significant positive results on operations. An increase in efficiency (reduction of data input time and stock management) and accuracy (reducing errors/losses), has an impact on customer satisfaction thanks to more accurate order status information. Its main achievements include the development and implementation of systems, effective user training, and comprehensive system testing. The benefits that are felt include increasing employee productivity, service quality, and business benefits through the lack of data errors.